Proceedings of the 4th International Symposium on Health Research (ISHR 2019) 2020
DOI: 10.2991/ahsr.k.200215.107
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Extract Cantigi (Vaccinium varingiaefolium) (Bl.) Miq and Its Major Compound of GC MS NIST Library Analysis

Abstract: Free Radical Damping Method (DPPH) The DPPH (2,2-diphenyl-1-pikrilhidrazil) method is one test to determine antioxidant activity. The DPPH method provides information on the reactivity of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Cantigi grows in the highlands and native plant from Indonesia and usually grows around volcanic craters, for example in Tangkuban Parahu (North Bandung), Mount Papandayan, and Mount Patuha (South Bandung) (4) . Research that has been conducted on phytochemical screening shows that cantigi leaves contain phytochemical compounds such as anthocyanins, chlorophyll, phenols, saponins, steroids, tannins, triterpenoids, and flavonoids (5) . Previous research showed cantigi leaves extract has antioxidant activity and an IC 50 of 16.84 ppm, which is categorized as having very strong antioxidant activity (6).…”
Section: Introductionmentioning
confidence: 99%
“…Cantigi grows in the highlands and native plant from Indonesia and usually grows around volcanic craters, for example in Tangkuban Parahu (North Bandung), Mount Papandayan, and Mount Patuha (South Bandung) (4) . Research that has been conducted on phytochemical screening shows that cantigi leaves contain phytochemical compounds such as anthocyanins, chlorophyll, phenols, saponins, steroids, tannins, triterpenoids, and flavonoids (5) . Previous research showed cantigi leaves extract has antioxidant activity and an IC 50 of 16.84 ppm, which is categorized as having very strong antioxidant activity (6).…”
Section: Introductionmentioning
confidence: 99%